Pollutants removal, microbial community shift and oleic acid production in symbiotic microalgae–bacteria system. (February 2023) - Hu, Hao; Wu, Dan-Dan; Yu, Li; Hu, Yi; Meng, Fan-Li; Wei, Dong
Graphical abstract: Highlights: The symbiotic MAS system improved nitrogen and phosphorus removal. Microalgae affected the abundance and species of fungi in MAS system. Pathogenic genes were reduced in MAS system. Bacteria promoted the production of oleic acid in MAS system. Abstract: The functional interaction between microorganisms is key in symbiotic microalga–bacteria systems; however, evaluations of fungi and pathogenic microorganisms are not clear. In this study, the roles of three groups ( i.e ., microalgae–activated sludge (MAS), Microalgae, and activated sludge) in pollutant removal and biomass recovery were comparatively studied. The data implied that microalgal assimilation and bacterial heterotrophic degradation were the major approaches for degradation of nutrients and organic matter, respectively. According to 16S rRNA and internal transcribed spacer sequencing, the relative abundance of Rhodotorula increased remarkably, favoring nutrient exchange between the microalgae and bacteria. The abundances of two types of pathogenic genes (human pathogens and animal parasites) were reduced in the MAS system. The oleic acid content in the MAS system (51.2 mg/g) was 1.7 times higher than that in the Microalgae system. The results can provide a basis for practical application and resource utilization of symbiotic microalgae–bacteria systems.